Lenalidomide and dexamethasone in relapsed/refractory immunoglobulin light chain (AL) amyloidosis: results from a large cohort of patients with long follow‐up. (3rd August 2021) - Basset, Marco; Kimmich, Christoph R.; Schreck, Nicholas; Krzykalla, Julia; Dittrich, Tobias; Veelken, Kaya; Goldschmidt, Hartmut; Seckinger, Anja; Hose, Dirk; Jauch, Anna; Müller‐Tidow, Carsten; Benner, Axel; et al.
Summary: Lenalidomide and dexamethasone (RD) is a standard treatment in relapsed/refractory immunoglobulin light chain (AL) amyloidosis (RRAL). We retrospectively investigated toxicity, efficacy and prognostic markers in 260 patients with RRAL. Patients received a median of two prior treatment lines (68% had been bortezomib‐refractory; 33% had received high‐dose melphalan). The median treatment duration was four cycles. The 3‐month haematological response rate was 31% [very good haematological response (VGHR) in 18%]. The median follow‐up was 56·5 months and the median overall survival (OS) and haematological event‐free survival (haemEFS) were 32 and 9 months. The 2‐year dialysis rate was 15%. VGHR resulted in better OS (62 vs. 26 months, P  < 0·001). Cardiac progression predicted worse survival (22 vs. 40 months, P  = 0·027), although N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP) increase was frequently observed. Multivariable analysis identified these prognostic factors: NT‐proBNP for OS [hazard ratio (HR) 1·71; P  < 0·001]; gain 1q21 for haemEFS (HR 1·68, P  = 0·014), with a trend for OS (HR 1·47, P  = 0·084); difference between involved and uninvolved free light chains (dFLC) and light chain isotype for OS (HR 2·22, P  < 0·001; HR 1·62, P  = 0·016) and haemEFS (HR 1·88, P  < 0·001; HR 1·59, P  = 0·008). Estimated glomerular filtration rate (HR 0·71, P  = 0·004) and 24‐h proteinuria (HR 1·10, P  = 0·004) were prognostic for renal survival. In conclusion, clonal and organ biomarkers at baseline identify patients with favourable outcome, while VGHR and cardiac progression define prognosis during RD treatment.